Better Than Its Reputation? Gossip and the Reasons Why We and Individuals With “Dark” Personalities Talk About Others - Hartung, Freda-Marie; Krohn, Constanze; Pirschtat, Marie (Frontiers in Psychology, 2019)
Gossip is an ubiquitous phenomenon. Hearing information about others serves important social functions such as learning without direct interaction and observation. Despite important social functions gossip has a rather negative reputation. Therefore, the present online study focuses on the reasons why people gossip and how these reasons are related to personality (i.e., dark triad) and situational settings. Six distinct motives were identified that underlie gossip behavior: information validation, information gathering, relationship building, protection, social enjoyment, and negative influence. The most important motive was validating information about the gossip target followed by the motive to acquire new information about the gossip target. The least important motive was harming the gossip target. The motivational pattern was highly similar between private and work context. Interestingly, the importance of motives mainly depends on the gossiper’s narcissism both in work and in private settings. The findings suggest that the negative reputation of gossip is not justified. In fact, even ‘dark’ personalities appear to use gossip to tune their picture of other humans and themselves and not to harm others.